If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.02(5000) + 0.03x = 0.025(5000 + x) Multiply 0.02 * 5000 100 + 0.03x = 0.025(5000 + x) 100 + 0.03x = (5000 * 0.025 + x * 0.025) 100 + 0.03x = (125 + 0.025x) Solving 100 + 0.03x = 125 + 0.025x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.025x' to each side of the equation. 100 + 0.03x + -0.025x = 125 + 0.025x + -0.025x Combine like terms: 0.03x + -0.025x = 0.005x 100 + 0.005x = 125 + 0.025x + -0.025x Combine like terms: 0.025x + -0.025x = 0.000 100 + 0.005x = 125 + 0.000 100 + 0.005x = 125 Add '-100' to each side of the equation. 100 + -100 + 0.005x = 125 + -100 Combine like terms: 100 + -100 = 0 0 + 0.005x = 125 + -100 0.005x = 125 + -100 Combine like terms: 125 + -100 = 25 0.005x = 25 Divide each side by '0.005'. x = 5000 Simplifying x = 5000
| 3(9)(8)(2)= | | 52=m-52 | | 2y-(7-4y)=10y-(y-2) | | 2x-6-6-0=4 | | x+25=86 | | 4(x+18)=2(4x+2) | | y-6=5 | | 8x=7x-16 | | x+23=94 | | n-9=15 | | -4x-16=-2x+4 | | 10(x^2-x-6)=1 | | b+8=31 | | x+38=59 | | 6(y-3)+3(y+5)=51 | | 1=-X^4 | | -13-x=-5x-1 | | 0=-X^4 | | -3x-4=14 | | -3(x-6)=-x-22 | | 13=10x-x^2 | | 4-3[3-(5y-5)]=0 | | 4(2x+3)=5x+15 | | 9x-27=0 | | 7(w-4)=w+2 | | 2(3x+4)-5(1-2x)=7(2x-3)+12 | | 6a+5=9 | | 9x+-2x=42 | | 5x+7-2x=4x+9-(-10) | | x^4-3X^2=0 | | 2z+9=z+3 | | 2x+y+3z=0 |